Comparison of Likelihood Ratios from Probabilistic Genotyping for Two-Person Mixtures across Different Assays and Instruments - McNevin, Dennis; Barash, Mark (Forensic sciences (Basel, Switzerland), 2024)
Continuous probabilistic genotyping (PG) provides a means to estimate the probative value of DNA mixtures tendered as evidence in court and subject to alternative propositions about the contributors to the mixtures. The weight of that evidence, however, may be valued differently, depending on which forensic laboratory undertook the DNA analysis. There is a need, therefore, to have a means for the comparison of likelihood ratios (LRs) generated by continuous PG amongst different laboratories for the same initial DNA sample. Such a comparison would enable the courts and the public to make judgements about the reliability of this type of evidence. There are particular mixtures and methods for which such a comparison is meaningful, and this study explores them for the short tandem repeat (STR) electropherograms of two-person mixtures obtained from the PROVEDIt Database. We demonstrate a common maximum attainable LR for a given set of common STR loci and a given DNA mixture that is consistent across three different STR profiling assays and two different capillary electrophoresis instruments.